Assessment of face mask use among peripartum women at mowbray maternity hospital during the covid-19 pandemic - Adusei, Samuel (Department of Obstetrics and Gynaecology, 2024)
Background: The current global COVID-19 pandemic has resulted in loss of life worldwide. According to the John Hopkins dashboard on COVID-19, 6 446 935 out of 595 645 271 infected patients lost their lives. There were 12 562 636 cases in Africa and 257 083 lost their lives as of 11th August 2022. South Africa recorded 4 007 080 cases with 101 982 mortalities and the Western Cape was one of the highest hit provinces in the same period (662 113 cases). Primary prevention for COVID-19 includes social distancing, hand washing, using alcohol- based hand sanitisers, and, mostly importantly, face mask use. Of these, face mask use is the least adhered to. Effective face mask use and reasons for use or non-use among a vulnerable population such as peripartum women are still unknown. Objective: To assess face mask use and associated factors among peripartum women at Mowbray Maternity Hospital during the COVID-19 pandemic. Method: An analytical cross-sectional study was used to assess the proportion of peripartum women who effectively wore face masks. Effective face mask use was measured with the WHO tool on mask usage in the context of COVID-19. A total of 500 women who visited the facility from the 1st of October 2020 to 31st October 2020 were first observed for effective face mask use before selection into the study to curb response bias. A structured interviewer-administered questionnaire was used to assess knowledge and perceived reasons for face mask use among 250 selected peripartum women. Data were analysed in STATA version 15.0. Frequencies and percentages were reported for categorical variables. Graphs and percentages were used to report the proportion of women who effectively used face masks in each of the stages of labour. The chi-square or Fisher's exact test (where necessary) were used to determine the association between effective face mask use and each independent variable. A multiple logistic regression model with a significance level set at p<0.05, was employed to determine the factors associated with effective face mask use. Results: Eighty-two percent of all women who visited the hospital wore their face mask effectively. Out of the 250 respondents, the proportion of effective face mask use was 78% (proportion = 78.0%; 95% CI = 72.3% - 83.0%); 90.0% had adequate knowledge of face mask use. More than half of the respondents, 133 (53.2%), agreed that they used face masks because they “felt susceptible to getting COVID-19 in the hospital”. One major reason for using face masks among most respondents ;227 (90.8%) was that “having COVID-19 will be troublesome as it may spread to loved ones”. Second/third stage of labour (aOR = 0.38; 95% CI = 0.17 - 0.83; p = 0.016), and secondary education (aOR = 0.25; 95% CI = 0.08 - 0.77; p = 0.016) were associated with ineffective mask usage, whereas disagreement with perception that pressure from mass media and government reminded them of the need to put on a face mask (aOR = 3.58; 95% CI = 1.44 - 8.93; p = 0.006), and adequate knowledge (aOR = 4.10; 95% CI = 1.49 - 11.28; p = 0.006) were factors associated with effective face mask use. Conclusion: Generally, effective face mask use was high amongst respondents but was lowest in the second/third stage of labour. Knowledge of effective face mask use was also high. Even though the use of face mask is of historic value now, it is worth noting these important factors associated with mask use, to ensure compliance during future respiratory pandemics like COVID-19. There is a need for health professionals at the hospitals to educate peripartum women with secondary education about the dangers of COVID-19 and the risk of spread, especially in the hospital